Constituição e angústia: um olhar a partir da Psicopatologia Fundamental - Omati, Adriana de Camargo Andrade (2014)
The present master´s degree dissertation intends to deepen the discussion about anxiety and its relation to the constitution of human and the I. In accordance with the Fundamental Psychopatology position, anxiety does not necessarily encapsulates itself in the realms of Pathology, and is one of the first criative outlets created by humans when faced with the crisis of the Myth of the Glacial Catastophe, being, therefore, one of the first defeses of the psychism. This resarch was motivated by the clinical experience of a therapeutic accompaniment of a yong woman, who was at the time confined to her house because of her fear of leaving the house and suffering from na anxiety attack of the street. This patient, who had been given a panic disorder diagnosis suffered tremendously when confronted with the idea of circulating on the outside world and also on her internal world, making it very difficult for the accompaniement to have any other function other then that of a physical and concrete presence to fend off axiety. So that one could understand why anxiety in the particular case carried such little criative potency for the transformation of pathos, references were searched in Psychology, Psychoanalysis, Psychiatry and Philosophy, in order to mantain a plural discourse following the Fundamental Psychopatology tradition to discuss the possible relations between anxiety and constitution